(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
New technology along with what patients want are making both the health care and retail pharmacy industries change quickly. Health care centers that offer a full range of services are turning into retail pharmacies. They provide medical care, individualized care, and help people deal with long-term illnesses. AI is helping people get the care they need, keeping patients safe, and making things run more smoothly. AI powered predictive analytics will help pharmacies avoid making mistakes with medications, better predict demand, keep their stock at the right levels, and make better use of their resources. Pharmacists can now treat and keep patients healthy from a distance thanks to virtual assistants and telehealth interoperability. It will be easier to handle paperwork and keep the pharmacy safe from problems in the supply chain if new technologies are used and the pharmacy is automated. AI will become even more important in pharmacy as deep learning, generative AI, and personalized medicine get better. AI-created digital twins will help doctors act like patients and improve clinical decision support systems for precision medicine. Autonomous AI systems will simplify inventory management and optimization. AI ethics will promote greater transparency and reduce bias within pharmacy services while ensuring pharmacy services remain within guidelines of standard operating procedures to remain safe and useful. AI telepharmacy and virtual care solutions will extend patient access to practicitioners and health services regardless of patients’ locations. All together, these trends represent a significant transition in the delivery of healthcare. Care will move from reactive, informed by data, and patient-centered to preventative, informed by data, and patient centered, will change the function role of retail pharmacy in the healthcare delivery model.